Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

Boosting the electromagnetic protective, thermal dissipative, mechanical, and waterproof properties of C/Co porous particles through Fe-doping and magnetic-field-orientation engineering - Ran Ji; Guiyue Zhou; Kaixin Liang; Zichu Xi; Shuhan Huang; Jiarui Yu; Yangbing Chen; Liyan Xie; Guoxiu Tong; Wenhua Wu (Chemical Engineering Journal, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Transcriptome Analysis Reveals Hyperglycemic Hormone and Excitatory Amino Acid Transporter 3 Are Involved in the Thermal Adaptation of Eriocheir sinensis - Xi Li; Runlin Zhou; Ruiqi Zhang; Zhen He; Mingzhi Zhang; Ran Li; Tong Hao; Jinsheng Sun (Fishes, 2025)
Temperature is one of the critical factors influencing the survival, growth, and reproduction of organisms. The molting and developmental mechanisms of crustaceans are highly sensitive to temperature, yet the regulatory mechanisms underlying their thermal adaptation remain unclear. In this work, transcriptome sequencing was performed to analyze the gene expression profiles of Eriocheir sinensis under normal temperature (22 °C) and high-temperature (27 °C and 32 °C) conditions. A total of 377 differentially expressed genes (DEGs) were identified, including 149 up-regulated and 227 down-regulated genes. Through Gene Ontology (GO) enrichment analysis of these DEGs, 11 significantly temperature-regulated signaling pathways were identified, including the estrogen and androgen receptor signaling pathways, and two neurotransmission signaling pathways. These findings suggest that temperature may influence sex regulation in E. sinensis, while the dopamine receptor and neuropeptide signaling pathways may play a role in its thermal adaptation. Further validation via RT-qPCR of DEGs involved in neurotransmission signaling pathways revealed that crustacean hyperglycemic hormone (CHH) and excitatory amino acid transporter 3 (EAA3) genes are likely involved in the thermal adaptation of E. sinensis. In addition, the hemolymph glucose levels associated with the elevated temperatures were detected and consistent variations between glucose levels and CHH expressions were found. This indicates that the eyestalk CHH is strongly correlated with the hemolymph glucose levels and likely mediates the response to temperature changes by regulating blood glucose in E. sinensis. The results of this study not only provide key molecular targets for elucidating the mechanisms by which temperature affects molting and development in E. sinensis, but also establish a theoretical foundation for further research into thermal adaptation strategies in crustaceans.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Ursolic acid, a potential anticancer compound for breast cancer therapy - Ran Yin; Tong Li; Jing Xin Tian; Pan Xi; Rui Hai Liu (Critical Reviews in Food Science and Nutrition, 2018)